Two new species of Kaempferia subgenus Kaempferia (Zingiberaceae: Zingibereae) from Thailand - PIYAPORN SAENSOUK; SURAPON SAENSOUK; THAWATPHONG BOONMA (Society for Indonesian Biodiversity, 2022)
Abstract. Saensouk P, Saensouk S, Boonma T. 2022. Two new species of Kaempferia subgenus Kaempferia (Zingiberaceae: Zingibereae) from Thailand. Biodiversitas 23: 4343-4354. Two new species of Kaempferia L., namely Kaempferia napavarniae Saensouk, P. Saensouk & Boonma, and Kaempferia sakonensis Saensouk, P. Saensouk & Boonma, are discribed here. The production of terminal inflorescences, covered by leaf sheaths, makes both species fall into the subgenus Kaempferia. The first species were found only in Nakhon Sawan Province, Northern Thailand, and the second species were found only in Sakon Nakhon Province, Northeastern Thailand. Living specimens and spirit specimens of both new species were compared to the existing allied species, but they differed and were never reported in taxonomic treatment before. Thus, we claimed both of them as new species to science and named the first species to honor Associate Professor Dr. Napavarn Noparatnaraporn (Director of Center for Research-driven in Natural Resources and Environment towards Utilization) who is a specialist in Biodiversity in Thailand. And named the second species according to its locality by using the province name as the epithet name. The descriptions with their illustrations, ecology, etymology, distributions, and a revised key to species of Kaempferia subgenus Kaempferia in Thailand for facilitating identification are also prepared.